Exploration of Novel Pathways Underlying Irreversible Electroporation Induced Anti-Tumor Immunity in Pancreatic Cancer - Imran, Khan Mohammad; Nagai-Singer, Margaret A.; Brock, Rebecca M.; Alinezhadbalalami, Nastaran; Davalos, Rafael V.; Allen, Irving Coy (Frontiers in Oncology, 2022)
Advancements in medical sciences and technologies have significantly improved the survival of many cancers; however, pancreatic cancer remains a deadly diagnosis. This malignancy is often diagnosed late in the disease when metastases have already occurred. Additionally, the location of the pancreas near vital organs limits surgical candidacy, the tumor’s immunosuppressive environment limits immunotherapy success, and it is highly resistant to radiation and chemotherapy. Hence, clinicians and patients alike need a treatment paradigm that reduces primary tumor burden, activates systemic anti-tumor immunity, and reverses the local immunosuppressive microenvironment to eventually clear distant metastases. Irreversible electroporation (IRE), a novel non-thermal tumor ablation technique, applies high‐voltage ultra-short pulses to permeabilize targeted cell membranes and induce cell death. Progression with IRE technology and an array of research studies have shown that beyond tumor debulking, IRE can induce anti-tumor immune responses possibly through tumor neo-antigen release. However, the success of IRE treatment (i.e. full ablation and tumor recurrence) is variable. We believe that IRE treatment induces IFNγ expression, which then modulates immune checkpoint molecules and thus leads to tumor recurrence. This indicates a co-therapeutic use of IRE and immune checkpoint inhibitors as a promising treatment for pancreatic cancer patients. Here, we review the well-defined and speculated pathways involved in the immunostimulatory effects of IRE treatment for pancreatic cancer, as well as the regulatory pathways that may negate these anti-tumor responses. By defining these underlying mechanisms, future studies may identify improvements to systemic immune system engagement following local tumor ablation with IRE and beyond.